Study and analysis of WO-CO Turning Tool Using Finite Element Method. Issue 1 (March 2020) - Dhengre, Nishant; Pradhan, M. K.; Katarne, Rajnish
Abstract: Machining is the most vital operation, widely used in the manufacturing industry to remove materials and to achieve the desired geometry. As with most engineering problems we want to get the uppermost return, with the least investment. In this case we want to minimize costs, while increasing cutting speeds. But the major challenge faced is about understanding the mechanics of machining and significant influence of tool geometry, cutting velocity, depth and feed for cut that can be iterated to bring the best in the process. In this study, emphasizes will be made on range of speed causing stress on turning tool during metal cutting. A model has been developed using ANSYS software that can help in understanding the machining process. A different approach is proposed which will lead to the minimization of the damage to work material as well as tool material and to increase the profit or minimizing manufacturing cost per unit. In cutting operation, the region near the tool tip is the most important region and conditions at the tool tip is examined with precision so that improvements in tool performance can be achieved. In the present work, study of tool wear caused by the change in cutting depth, feeding rate and speed of cutting of single point cutting tool for a turning operation to predict the tool life in orthogonal cutting using Finite Element Method (FEM) is carried out. A simulation model was developed using ANSYS software in order to estimate the magnitude of the von-misses and residual stresses evolved during the machining process. The result shows the influence of depth during cut in the machining and influence of induced stresses on carbide tool. The result obtained have been verified by the available results from the literature for the variation of x-y stress, von-misses stress with the temperature, on carbide tool and was found to be in good agreement.